Interaction of menstrual cycle phase and sexual activity predicts mucosal and systemic humoral immunity in healthy women - Lorenz, Tierney K. (Physiol Behav, 2015)
Several studies have documented shifts in humoral immune parameters (e.g., immunoglobulins) across the menstrual cycle in healthy women. It is thought that these shifts may reflect dynamic balancing between reproduction and pathogen defense, as certain aspects of humoral immunity may disrupt conception and may be temporarily downregulated at ovulation. If so, one could expect maximal cycle-related shifts of humoral immunity in individuals invested in reproduction – that is, women who are currently sexually active – and less pronounced shifts in women who are not reproductively active (i.e., abstinent). We investigated the interaction of sexual activity, menstrual cycle phase, and humoral immunity in a sample of 32 healthy premenopausal women (15 sexually active, 17 abstinent). Participants provided saliva samples during their menses, follicular phase, ovulation (as indicated by urine test for LH surge), and luteal phase, from which IgA was assayed. Participants also provided blood samples at menses and ovulation, from which IgG was assayed. Sexually active participants provided records of their frequency of sexual activity as well as condom use. At ovulation, sexually active women had higher IgG than abstinent women (d = 0.77), with women reporting regular condom use showing larger effects (d = 0.63) than women reporting no condom use (d = 0.11). Frequency of sexual activity predicted changes in IgA (Cohen’s f(2) = 0.25), with women reporting high frequency of sexual activity showing a decrease in IgA at ovulation, while women reporting low frequency or no sexual activity showing an increase in IgA at ovulation. Taken together, these findings support the hypothesis that shifts in humoral immunity across the menstrual cycle are associated with reproductive effort, and could contribute to the mechanisms by which women’s physiology navigates tradeoffs between reproduction and immunity.